FREE Registration for online tutoring and homework help.

Solve this problem by using elimination: 2x-3y=61 and 2x+y=-7

Saturday, July 24th, 2010


  1. 2x –  =y=61
  2. 2x +   y= -7

If you subtract the second equation from the first, you can eliminate x and you are left with -4y = 68.

So y =3D -17, and plugging this into the first equation we can figure out

y:  2x = (-51)=61,

so x = 5

This entry was posted on Saturday, July 24th, 2010 at 2:41 am and is filed under 9th Grade, Homework Answers, Math Answers. You can follow any responses to this entry through the RSS 2.0 feed. You can leave a response, or trackback from your own site.

Leave a Reply